Factors Affecting the Development and Management of Smart City Approach Using a Combination of Big Data and the Internet of Things and Cloud Computing Technologies - Ghodsiyeh Fahmfam; Hodjat Hamidi (Iranian Journal of Information Processing & Management, 2019)
Smart city has shown a new form of life development in recent years and has been proposed as an effective approach to better urban management. Conceptually, in these types of cities, the interactions between the new technologies, the new organizations and the new constructive cities of smart cities have been integrated into the social and technical system. The goal of smart city is to realize the integration of urban business, transportation, water, energy and other urban sub-systems through the integration and analysis of data collected through sensors and information and communication technology (ICTs). In this paper, a hybrid structure is proposed using cloud computing and cloud processing and Internet technology for development and management of smart cities and urban planning. In addition, an assessment of sensor development and analysis, and the purpose of building smart cities as well as supporting technologies in these types of cities have been investigated. The present study aims at defining and reviewing large data and objects of the Internet and cloud computing, and identifying existing challenges and constraints. The proposed model structure has 3 layers: the first layer has the task of collecting large data sources and producing content. The second layer is responsible for linking and enhancing sensors and managing data and data processing using the Hadoop architecture. The third layer is responsible for applications and how to use the results and analytical data. The implementation of this system involves various stages of generating, collecting, integrating, classifying, processing, calculating and deciding information. Based on the information and analysis collected and the architecture of the system in question, the system uses Hadoop single-player in Ubuntu 14.04 LTS. It has been developed with 3.2 GHZ x4 processors and 4 GB of memory. Ultimately, this article has created a new way in the Internet context of objects, where data is gathered from different geographic locations using devices and sensors, and it uses a new system designed and cloud computing services in a city to analyze and cause smart decision making for smart city management and welfare of citizens.